Inhibiting lipolytic haloarchaeal damage on brine cured hides with halocin producer strains - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2007)
The Kaldirim and Kayacik Salterns of Tuz Lake in Central Anatolia are the main salt sources of Turkey. 55% of the salt requirements of Turkey is supplied from these safterns. 492 000 and 620 000 tons of salt were produced from Kaldirim and Kayacik Salterns in 2004, respectively. Crude salt extracted from these salt sources is commonly used in hide preservation. Lipolytic extremely halophilic Archaea found in the salt may reduce hide quality. Therefore, a microbial survey was conducted to examine lipolytic activities of the strains isolated from Kaldirum and Kayacik Salterns and determine whether or not halocins which were produced by the strains of Kaldirim and Kayacik Salterns may be used to inhibit lipolytic haloarchaeal strains in brine solutions. The levels of lipase producer strains in the both salterns was found to be almost similar. 39% of Kaldirim Saltern's strains and 43% of Kayacik Saltern's strains produced lipase. 89% of Kaldirim Saltern's strains and 29% of Kayacik Saltern's strains produced halocins effective against each other. It was found that lipase negative halocin producers of both Kaldirim and Kayacik Salterns were able to inhibit lipase positive strains in these salterns. Hence, it is recommended that lipase negative halocin producers or their halocin extracts may be used in preventing the haloarchaeal deterioration that can occur during brine curing of hides when using crude salt from whatever source.
Keywords: QUALITY